Local Impact of State Testing in Southwest Washington - Mabry, Linda; Poole, Jayne; Redmond, Linda; Schultz, Angelia (Education Policy Analysis Archives, 2003)
A decade after implementation of a state testing and accountability mandate, teachers' practices and perspectives regarding their classroom assessments and their state's assessments of student achievement were documented in a study of 31 teachers in southwest Washington state. Against a background of national trends and standards of psychometric quality, the data were analyzed for teachers' beliefs and practices regarding classroom assessment and also regarding state assessment, commonalities and differences among teachers who taught at grade levels tested by the state and those who did not, teachers' views about the impact of state assessment on their students and their classrooms, and their views about whether state testing promoted educational improvement or reform as intended. Data registered (1) teachers' preferences for multiple measures and their objections to single-shot high-stakes testing as insufficiently informative, unlikely to promote valid inferences of student achievement, and often distortive of curriculum and pedagogy; (2) teachers' objections to the state test as inappropriate for nonproficient speakers of English, for students eligible for special services, and for impoverished students; and (3) teachers' preferences for personalized assessments respectful of student circumstances and readiness, rather than standardized assessments. Teachers' practical wisdom thus appeared more congruent than the state testing program with measurement principles regarding (1) multiple methods and (2) validation for specific test usage, including usage with disadvantaged subgroups of test-takers. Findings contrasted a distinction of emphasis: state focus on "testing students" as distinct from teachers' focus on "testing students."